(untitled) (Interdisciplinary Research in Education, 2025)
This paper examines the challenges in teaching social studies and life skills education in secondary schools within Melamchi Municipality, Bagmati Province. Using a qualitative approach, data were collected from four secondary-level teachers through semi-structured interviews. A purposive sampling technique was used to select schools. An interview guideline was applied to the participants in this study. After collecting data, an analysis of the data was made through the interpretation of the raw data by the interpretative method. The results reveal that the challenges of teaching social studies and life skills education are overloaded and outdated curriculum, teaching and learning resources, teacher capacity and training programs, lack of field-based and experiential learning, assessment and evaluation issues, societal and cultural barriers, and school and administrative support, selection and teaching current events and controversial issues in the classroom. The findings indicate that there are necessary improvements in the curriculum, including better training for teachers, a more interactive approach that focuses on field-based and experiential learning, improved assessment, and supplements to instructional resources.